2013
DOI: 10.1111/1556-4029.12260
|View full text |Cite
|
Sign up to set email alerts
|

Deaths Involving Methylenedioxypyrovalerone (MDPV) in Upper East Tennessee

Abstract: Two deaths involving 3, 4-methylenedioxypyrovalerone (MDPV) are reported. MDPV is a synthetic cathinone stimulant found in "bath salts" with neurological and cardiovascular toxicity. Biological specimens were analyzed for MDPV by GC/MS and LC/MS. A White man was found dead with signs of nausea and vomiting after repeatedly abusing bath salts during a weekend binge. Femoral venous blood and urine had MDPV concentrations of 39 ng/mL and 760 ng/mL. The second fatality was a White man with a history of drug and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…In relation to these findings, Wakeford and Riley suggested the possibility that these strains do not differ in their sensitivity to emetic or sickness-inducing agents. Interestingly, clinical reports have shown that MDPV use has been associated with symptoms of nausea and vomiting (Coppola and Mondola, 2012; Wright et al, 2013). Although these findings suggest that the failure to see strain differences in MDPV-induced avoidance may be related to its sickness-inducing effects, it will be important to validate such effects in preclinical models of emesis and palatability shifts (see Parker, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to these findings, Wakeford and Riley suggested the possibility that these strains do not differ in their sensitivity to emetic or sickness-inducing agents. Interestingly, clinical reports have shown that MDPV use has been associated with symptoms of nausea and vomiting (Coppola and Mondola, 2012; Wright et al, 2013). Although these findings suggest that the failure to see strain differences in MDPV-induced avoidance may be related to its sickness-inducing effects, it will be important to validate such effects in preclinical models of emesis and palatability shifts (see Parker, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The non-medical use of psychoactive synthetic cathinones, commonly known as “bath salts,” has increased worldwide in recent years (Baumann, 2014; German et al, 2014), often leading to life-threatening medical consequences (Kesha et al, 2013; Wright et al, 2013). Three of the most popular synthetic cathinones, 3,4-methylenedioxypyrovalerone (MDPV), 4-methyl- N -methylcathinone (mephedrone) and 3,4-methylenedioxy- N -methylcathinone (methylone), have been classified by the United States (US) as Schedule I controlled substances (Drug Enforcement Administration, 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects include agitation, combative or violent behavior, psychosis, hallucinations, delusion, paranoia, confusion, suicidal ideation, tachycardia, chest pains, hypertension, dehydration, cardiovascular complications, rhabdomyolysis, and even death (27)(28)(29). In a Michigan study conducted by the Centers for Disease Control and Prevention from November 13, 2010 to March 31, 2011, 17 of the 35 emergency room patients exposed to synthetic cathinones were hospitalized, and one was dead upon arrival at the emergency room (30).…”
Section: Discussionmentioning
confidence: 99%